Tracking Boats on Amazon Rivers—A Case Study with the LoRa/LoRaWAN - Marlos Rodrigues; Alyson dos Santos; Hillermann Lima; Warley Nogueira; Vicente de Lucena Junior (Sensors)
The Amazon region has the largest hydrographic basin in the world. The rivers act as roads, and boats serve as vehicles for transporting passengers and cargo to large urban centers, municipalities, riverside communities, villages, and settlements. The Amazon River transportation system faces critical gaps due to the lack of land infrastructure in certain areas, which makes rivers essential for commerce and access to isolated communities. This work proposes the development of a new hardware platform consisting of a system-in-package (SiP)—iMCP HTLRBL32L and GPS, which enables data transfer over a network with long-range LoRa technology. In addition, we developed a new communication protocol between the end devices called the LoRa Protocol Proprietary (LPP). This protocol allows parameterizable commands (location table, modulation, routing, source and destination DevEUI, and port) to be sent between end devices, providing flexibility in the configuration and management of Internet of Things networks. The results of the practical experiments with the new hardware platform in the communication scenario between the end device and the gateway show that the maximum range was 16.928 km. In the communication scenario between the end devices, the maximum range was 12.447 km. It offers a stable platform for exchanging control information, which is fundamental to the safety of river transport in the Amazon.